THE MOMENT INTEGRATED SOLUTION METHOD IN MULTI–CRITERIA DECISION–MAKING - Akan, Ercan; Bayar, Sibel; Elmas, Güldem (International Journal of Industrial Engineering: Theory, Applications and Practice, 2021)
In this study, the aim was to develop a new method called The Moment Integrated Solution (THEMIS) method, inspired by moment as used in Physics, and is proposed to solve Multi-Criteria Decision-Making (MCDM) problems. The most important characteristic of the proposed method is based on the pairwise comparison by computing THEMIS method taking the value of [0,1]. According to THEMIS method, firstly, pairwise comparison criteria that have been evaluated by the decision-maker are computed by THEMIS, thereby creating a decision matrix that will be computed by THEMIS method. Finally, the scores of the alternatives are derived by aggregating the weights from different sets of criteria and alternatives, based on whichever best alternative is selected. To analyze the proposed method and evaluate its performance, by computing both the Analytical Hierarchy Process (AHP) and THEMIS methods, we carried out some numerical examples, such as 'a family's house buying' in the literature. The 'mobile telephone selection' problem in the literature was analyzed statistically, and the proposed method with a 5x5 matrix was simulated. THEMIS method has given better results, albeit with small differences. However, it should be noted that the improvement is not a significant percentage. It was observed that the method has the capability to accurately rank alternatives and criteria as well as AHP. It is considered that the methodological contribution of the proposed method brings a new approach to group decision-making. It can also be considered as an alternative method under MCDM.